A VLP-based vaccine against interleukin-1α protects mice from atherosclerosis. - Tissot, A; Spohn, G; Jennings, G; Shamshiev, A; Kurrer, M; Windak, R; Meier, M; Viesti, M; Hersberger, M; Kündig, T; Ricci, R; Bachmann, M (2013)
Interleukin (IL)-1α is a potent proinflammatory cytokine that has been implicated in the development of atherosclerosis. We investigated whether a vaccine inducing IL-1α neutralizing antibodies could interfere with disease progression in a murine model of atherosclerosis. We immunized Apolipoprothin E (ApoE)-deficient mice with a vaccine (IL-1α-C-Qβ) consisting of full-length, native IL-1α chemically conjugated to virus-like particles derived from the bacteriophage Qβ. ApoE(-/-) mice were administered six injections of IL-1α-C-Qβ or nonconjugated Qβ over a period of 160 days while being maintained on a western diet. Atherosclerosis was measured in the descending aorta and in cross-sections at the aortic root. Macrophage infiltration in the aorta was measured using CD68. Expression levels of VCAM-1, ICAM-1, and MCP-1 were quantified by RT-PCR. Immunization against IL-1α reduced plaque progression in the descending aorta by 50% and at the aortic root by 37%. Macrophage infiltration in the aorta was reduced by 22%. Inflammation was also reduced in the adventitia, with a decrease of 54% in peri-aortic infiltrate score and reduced expression levels of VCAM-1 and ICAM-1. Active immunization targeting IL-1α reduced both the inflammatory reaction in the plaque as well as plaque progression. In summary, vaccination against IL-1α protected ApoE(-/-) mice against disease, suggesting that this may be a potential treatment option for atherosclerosis.